Analysis of Factors that Influence Millennial and Generation Z Investment Decisions - Afiani, Mirza Zulmi; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Utami, Restu Frida (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify the factors that influence investment decisions for millennials and Generation Z in Purwokerto. The quantitative method was used in this study, and primary data was collected through a survey. The population of this research is millennials and Generation Z in Purwokerto, which comprises 125 respondents. IBM SPSS Statistics 26 was used to analyse the research data to conclude. The results stated that financial literacy, overconfidence, herding, and risk tolerance positively affect investment decisions. This is because millennials and Generation Z have sound economic knowledge, high confidence in making decisions, have people as a reference in taking action, and see risks when deciding to invest. Meanwhile, risk perception hurts millennial and Generation Z investment decisions in Purwokerto.